2022
DOI: 10.1007/s00392-022-02102-2
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic affects STEMI numbers and in-hospital mortality: results of a nationwide analysis in Germany

Abstract: Background The COVID-19 pandemic led to extensive restrictions in Germany in 2020, including the postponement of elective interventions. We examined the impact on ST-elevation myocardial infarction (STEMI) as an acute and non-postponable disease. Methods Using German national records, all STEMI between 2017 and 2020 were identified. Using the number of STEMI cases between 2017 and 2019, we created a forecast for 2020 and compared it with the observed numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Values of stroke in TA-TAVR could not be calculated due to a stroke rate of 0.00% in TA-TAVR. patients (14), lower numbers could have been expected, as this also was observed in acute ST-elevation myocardial infarction (15). Furthermore, in contrast to a previously stated rise of TA-TAVR procedures (5), we now observe noticeably fewer cases compared to the steadily increasing TF-TAVR numbers.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Values of stroke in TA-TAVR could not be calculated due to a stroke rate of 0.00% in TA-TAVR. patients (14), lower numbers could have been expected, as this also was observed in acute ST-elevation myocardial infarction (15). Furthermore, in contrast to a previously stated rise of TA-TAVR procedures (5), we now observe noticeably fewer cases compared to the steadily increasing TF-TAVR numbers.…”
Section: Discussionsupporting
confidence: 43%
“…Nevertheless, compared to a previous analysis of TAVR in aortic regurgitation in Germany from 2008 to 2015 ( 5 ), we see a further growth of TAVR procedures. The increased TAVR numbers in 2020 are particularly surprising: Due to the COVID-19 pandemic with lockdown restrictions in 2020 in Germany, including postponing elective procedures to provide hospital resources for COVID-19 patients ( 14 ), lower numbers could have been expected, as this also was observed in acute ST-elevation myocardial infarction ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Furnica et al [ 37 ] found that the incidence of STEMI decreased by 48.8% during the COVID-19 pandemic compared to the same time in the previous year[ 37 ]. Another study by Oettinger et al [ 38 ] reported a similar increase in STEMI incidence of 22.9% during the COVID-19 pandemic[ 38 ]. These findings suggest that there may be an association between the declining incidence of STEMI and the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 85%